Biomaterials and bionanotechnology - Tekade, Rakesh K. (Advances in pharmaceutical product development and research series., 2019)
Biomaterials and Bionanotechnology examines the current state of the field within pharmaceutical sciences and concisely explains the history of biomaterials including key developments. Written by experts in the field, this volume within the Advances in Pharmaceutical Product Development and Research series deepens understanding of biomaterials and bionanotechnology within drug discovery and drug development. Each chapter delves into a particular aspect of this fast-moving field to cover the fundamental principles, advanced methodologies and technologies employed by pharmaceutical scientists, researchers and pharmaceutical industries to transform a drug candidate or new chemical entity into a final administrable dosage form, with particular focus on biomaterials and bionanomaterials. This book provides a comprehensive examination suitable for researchers working in the pharmaceutical, cosmetics, biotechnology, food and related industries as well as advanced students in these fields.